In silico screening and identification of lead molecules from Garcinia gummi-gutta with multitarget activity against SARS-CoV-2 - Keerthi J. Sugathan, Sivanandan Sreekumar, Biju Charuvila Kamalan (Journal of Applied Pharmaceutical Science, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19, has affected the human population, resulting in multiple waves of pandemics around the world. One of the main threats is hyper-evolved viral variants with high transmissibility and virulence, and the best solution is the application of multitargeted drugs of plant origin. In this perspective, the anti-SARS-CoV-2 activity of Garcinia gummi-gutta was evaluated through an in silico approach. A total of 97 phytochemicals from G. gummi-gutta were tested against three therapeutic targets of SARS-CoV-2, namely spike protein, main protease (Mpro), RNA-dependent RNA polymerase, and two human host targets such as angiotensin-converting enzyme-2 and nuclear factor-κB through molecular docking. Out of 97 phytochemicals screened, 18 of them showed significant binding free energy with all the five selected targets. The compound amentoflavone was chosen as the best lead molecule based on binding energy, molecular interactions, and absorption distribution metabolism and excretion profile. The interaction of amentoflavone with Mpro was further verified using molecular dynamic simulation. The overall results revealed that the compound amentoflavone can be recommended as the best lead compound with multitargeting potential against SARS-CoV-2, and can be recommended for further experimental studies leading to drug discovery.
Keywords: SARS-CoV-2, Garcinia gummi-gutta, docking, molecular dynamic simulation, phytochemicals